2005
DOI: 10.1021/jf048616l
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry and Its Anthocyanins Reduce Oxidative Stress-Induced Apoptosis in PC12 Cells

Abstract: Because strawberries are known to contain higher concentrations of phytochemicals and have higher antioxidant capacity among common fruits, their neuroprotective activity was tested in vitro on PC12 cells treated with H2O2. Their protective effect and antioxidant capacity were also compared with those of banana and orange, which are the fresh fruits consumed at highest levels in the United States. The cell viability test using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 39 publications
(47 reference statements)
5
87
1
3
Order By: Relevance
“…Strawberry fruit also have high ascorbic acid concentrations which have protective roles against reactive oxygen species (17). As major contributors to the total phenolic contents, as well as important to fruit color, anthocyanins also have potent antioxidant properties (18) and reduce oxidative stress-induces neurotoxicity (19). Strawberry is reported to serve as one of our most important dietary sources of phenolic compounds (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry fruit also have high ascorbic acid concentrations which have protective roles against reactive oxygen species (17). As major contributors to the total phenolic contents, as well as important to fruit color, anthocyanins also have potent antioxidant properties (18) and reduce oxidative stress-induces neurotoxicity (19). Strawberry is reported to serve as one of our most important dietary sources of phenolic compounds (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have shown that daily supplementation of blueberry (27) and Concord grape (28) juice for 12 weeks enhanced cognitive performances in elderly participants displaying mild cognitive impairments (MCI) in comparison to that of the placebo-supplemented participants. Similar sets of in vitro studies have demonstrated that the antioxidant polyphenol anthocyanin in blueberries and strawberries can attenuate oxidative stress mediated by cytotoxic stimuli (29,30) . From this research, it can be concluded that dietary interventions could provide promising therapeutic potentials to modulate aberrant histone PTMs (4) and alleviate oxidative stress syndromes (31) associated with neurodegenerative diseases.…”
Section: Epigenetics and Gene Expressionmentioning
confidence: 72%
“…Sólidos solúveis e relação SS/AT nos frutos do morango em função das doses de Si e modo de aplicação. As antocianinas são pigmentos importantes para a saúde humana, pois apresentam considerável capacidade de sequestrar radicais livres, evitando danos celulares e prevenindo doenças degenerativas (MEYERS et al, 2003;HEO;LEE, 2005) e comercialmente a coloração dos frutos, pode ser influenciada pelas antocianinas o que contribui muito para a avaliação da qualidade, pois os consumidores fazem correlações entre a cor e a qualidade total de produtos específicos (KAYS, 1999). Valores de antocianinas em morangos são encontrados na literatura, tais como os reportados por Zhang, Vareed e Nair (2005) A relação SS/AT, que representa a proporção entre os teores de ácidos e açúcares existentes nos frutos, condicionando a sua qualidade organoléptica, isto é, o balanço entre sabor e aroma, não apresentaram diferenças significativas entre as doses de Si, para ambos os modos de aplicação (Tabela 3).…”
Section: Estas Variáveis Foram Influenciadas Pelas Doses Deunclassified